2004
DOI: 10.1590/s0074-02762004000200010
|View full text |Cite
|
Sign up to set email alerts
|

A contribution to the diagnosis of Capillaria hepatica infection by indirect immunofluorescence test

Abstract: A highly specific pattern of immunofluorescence was noted when sera from Capillaria hepatica-infected rats were tested against the homologous worms and eggs present either in paraffin or cryostat sections from mouse liver. The pattern was represented by a combined apple green fluorescence of the internal contents of worms and eggs, which persisted in serum-dilutions of 1:400 up to 1:1600. Unequivocal fluorescent pattern was observed from 15 days up to 3 months following inoculation of rats with embryonated C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 14 publications
0
9
0
2
Order By: Relevance
“…Maintenance of immunofluorescence at these dilutions is considered to be specific for Capillaria hepatica [19]. Of these, only 2 sera (one 4 years-old boy and one 34 years-old woman) remained positive after the dilution to 50% with PBS, thus characterizing a strong seroprevalence of only 0.81% among the sampled population.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Maintenance of immunofluorescence at these dilutions is considered to be specific for Capillaria hepatica [19]. Of these, only 2 sera (one 4 years-old boy and one 34 years-old woman) remained positive after the dilution to 50% with PBS, thus characterizing a strong seroprevalence of only 0.81% among the sampled population.…”
Section: Resultsmentioning
confidence: 99%
“…An experimental study with Wistar rats [19] confirmed the excellent sensitivity and specificity of the indirect immunofluorescense technique and estimated that positivity starts 15 days after infection and lasts for three months. In false-positive cases (ingestion of non- embryonated eggs) reactions are initially positive; however, dilutions equal or greater than 1/400 show a negative reaction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… Em concordância com sugestão de Assis et al (2004), considerando a alta prevalência de infecção por C. hepatica de ratos nas grandes cidades e as más condições de higiene, que tantas vezes, prevalecem nos arredores das populações urbanas pobres, parece lógico suspeitar que as infecções humanas com este helminto possam ocorrer em tal ambiente. Um bom teste sorológico para o diagnóstico de infecção por C. hepatica poderia ser incluído no diagnóstico diferencial quando crianças ou mesmo adultos apresentarem hepatoesplenomegalia, febre inexplicável e eosinofilia.…”
Section: Conclusãounclassified